Bio equivalence Study of Two Tablet Formulations of Sildenafil - Franco Spínola, Ana Cristina; Almeida, Susana; Filipe, Augusto; Tanguay, Mario; Yritia, Mercedes (Arzneimittelforschung, 2008)
This study was conducted in order to assess the bioequivalence of two tablet formulations containing 100 mg sildenafil (1-[4-ethoxy-3-(6,7-dihydro-l-,ethyl-7-oxo-3-propyl-lH-pyrazolo[4,3-d]pyrimi-din-5-yl)phenylsulphonyl]-4-methyl piperazine, CAS 139755-83-2). Twenty-eight healthy subjects were enrolled in a single-centre, randomised, single-dose, open-label, 2-way crossover study, with a minimum washout period of 7 days. Plasma samples were collected up to 18.0 h post-dosing. Sildenafil levels were determined by reverse liquid chromatography coupled with tandem mass spectrometry detection (LC-MS/MS). Pharmacokinetic parameters used for bioequivalence assessment [area under the concentration-time curve from time zero to time of last nonzero concentration (AUClast) and maximum observed concentration (Cmax) were main evaluation criteria; however, the area under the concentration-time curve from time zero to infinity (AUCinf) was also analysed] were determined from the sildenafil concentration data using non-compartmental analysis. The 90% confidence intervals (obtained by analysis of variance, ANOVA) were 86.70–108.19 for Cmax, 86.67–99.26 for AUClast and 87.19–99.82 for AUCinf, within the predefined ranges. Bioequivalence between the two formulations was concluded both in terms of rate and extent of absorption.
Keywords: CAS 139755-83-2; Phosphodiesterase type 5, inhibitors; Sildenafil, bioequivalence, pharmacokinetics